(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Yoga practices have been increased around the world due to perceived benefits of meditation for stress management. It has a positive impact on stress level in yoga practitioners. Yoga activities provide a sense of well-being, which leads to an increase in self-esteem and relaxation. Banking personnel often have a high degree of stress due to work pressure they confront in their job. Stress lowers a person’s ability and a healthy employee ensures productive outcome in the organization. MATERIALS AND METHODS: A cross sectional descriptive research design was used and this study was confined to employees of different banks situated at Janakpurdham, Nepal. The duration of the study was from August 2020 to September 2020. A total of 205 participants were randomly selected. Simple random sampling technique was used to select banks of Janakpurdham from the list papered for the purpose of data collection. RESULTS: There was strong association between demographic variables and perception of yoga, regarding mental and physical health among the bank employees. The perceived benefits of yoga on physical health as well as mental health for stress management was found to be associated with socioeconomic characteristics of the participants such as gender, religion, level of education, family income (p<0.05), except for age group and marital status (p>0.05). CONCLUSIONS: This study found that yoga keeps persons active for whole day, as well as yoga is beneficial for stress management too. Yoga is effective in lowering occupational stress, hence yoga awareness program among bank personnel is necessary.